2015
DOI: 10.1016/j.cub.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution of Species Recognition

Abstract: Sex with another species can be disastrous, especially for organisms that mate only once, like yeast. Courtship signals, including pheromones, often differ between species and can provide a basis for distinguishing between reproductively compatible and incompatible partners. Remarkably, we show that the baker's yeast Saccharomyces cerevisiae does not reject mates engineered to produce pheromones from highly diverged species, including species that have been reproductively isolated for up to 100 million years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…First, these variants did not result in constitutive signalling, indicating that overall pathway responsiveness was preserved. Second, the frequency and the morphology of mating projections in cells expressing truncated receptors were undistinguishable from those of wild-type cells, in agreement with a recent study that found that truncated variants can mediate mating 60 . Third, pathway deactivation proceeded normally in truncation mutants, provided that the receptor's interaction with the pheromone was weak.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, these variants did not result in constitutive signalling, indicating that overall pathway responsiveness was preserved. Second, the frequency and the morphology of mating projections in cells expressing truncated receptors were undistinguishable from those of wild-type cells, in agreement with a recent study that found that truncated variants can mediate mating 60 . Third, pathway deactivation proceeded normally in truncation mutants, provided that the receptor's interaction with the pheromone was weak.…”
Section: Discussionsupporting
confidence: 89%
“…Mating projections are a critical step in the fusion of haploid yeast cells, the end goal of mating pathway activation 18 . While full C-terminal truncations strongly affect shmoo orientation toward potential mates, the impact of partial truncations is less severe and they permit mating 59 60 . Recent work demonstrated that Sst2's RGS activity, but not its interaction with Ste2, is required for proper mating orientation 61 .…”
Section: Resultsmentioning
confidence: 99%
“…The features of α-factor required for binding to its orthosteric site and for activation of Ste2 have been explored by examining structure-activity relationships in peptide agonists and antagonists derived by genetic methods ( 6 ) and by chemical synthesis ( 7 ). Similarly, the properties of the receptor and the residues involved in its folding, membrane trafficking, and ligand discrimination have been extensively studied by both targeted and unbiased mutagenesis ( 8 10 ). As for other GPCRs, there is some evidence that Ste2 function can be influenced by compounds binding to allosteric sites ( 11 , 12 ).…”
Section: Yeast Pheromone Receptorsmentioning
confidence: 99%
“… Number of α-factor-encoding repeats in MF α1 predicts pheromone secretion rates measured in natural isolates. Pheromone secretion rates (molecules cell-1 sec-1) were measured by ELISA ( Rogers et al 2012 ) in haploid MATα strains derived from natural isolates belonging to three independent lineages: (A) S. cerevisiae Wine/European, (B) S. paradoxus American C, and (C) S. paradoxus European. Vertical dashed lines separate groups of strains within each lineage with different repeat numbers or sequences (as indicated in the top left of each section).…”
Section: Resultsmentioning
confidence: 99%